The C++ programming language - Stroustrup, Bjarne
"This is a complete rewrite of the most widely read and most trusted book on C++. Based on the ANSI/ISO C++ final draft, this book covers the C++ language, its standard library, and key design techniques as an integrated whole." "The C++ Programming Language provides comprehensive coverage of C++ language features and standard library components." "With this third edition, Stroustrup makes C++ even more accessible to those new to the language while adding information and techniques that even expert C++ programmers will find invaluable."--Jacket.